Reduction of Gastric Haemorrhage by Fibrinolysis Inhibition – An Experimental Study in Rats - Stenberg, Björn; Karlsson, Lilian; Alpsten, Magne; Risberg, Bo (Thrombosis and Haemostasis, 1983)
Gastric ulcerations were induced in rats by pyloric ligature and instillation of 1.0 N HCl. After four hours all rats had developed ulcerations. Increased release of plasminogen activators from the mucosa during these conditions has previously been demonstrated. In the present study we investigated the role of fibrinolysis inhibition versus Hz-receptor blockade on the gastric bleeding. Tranexamic acid – a synthetic inhibitor of the fibrinolytic system – was found to significantly (p <0.01) reduce blood loss into the gastric juice by 30% measured by 51Cr labelled red blood cells; cimetidine did not reduce the gastric haemorrhage under the experimental conditions used. Both treatment regimes significantly (p <0.02) reduced the secretion of gastric juice. These results indicate a contribution of the fibrinolytic system in gastric bleeding from experimentally induced gastric ulcerations.
Keywords: Gastric haemorrhage; Fibrinolysis; Plasminogen activator; Antifibrinolysis